2020
DOI: 10.1101/2020.12.01.20242321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 29-mRNA Host Response Test from Blood Accurately Distinguishes Bacterial and Viral Infections Among Emergency Department Patients

Abstract: Study designWhether or not to administer antibiotics is a common and challenging clinical decision in patients with suspected infections presenting to the emergency department (ED). We prospectively validate InSep, a 29-mRNA blood-based host response test for the prediction of bacterial and viral infections.MethodsThe PROMPT trial is a prospective, non-interventional, multi-center randomized, controlled clinical trial that enrolled 397 adult patients presenting to the ED with signs of acute infection and at le… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Proprietary machine learning classifiers were used to process gene expression level data (24) and to generate three separate, prespecified scores for the likelihoods of (1) bacterial infection, (2) viral infection, and (3) severe outcome. The performance of the algorithms for determining the likelihood of bacterial and viral infection (IMX-BVN-2) has been previously described elsewhere (25) and in the same Greek ED patient cohort (26). The current study therefore focused on the performance of the severity risk score.…”
Section: Introductionmentioning
confidence: 99%
“…Proprietary machine learning classifiers were used to process gene expression level data (24) and to generate three separate, prespecified scores for the likelihoods of (1) bacterial infection, (2) viral infection, and (3) severe outcome. The performance of the algorithms for determining the likelihood of bacterial and viral infection (IMX-BVN-2) has been previously described elsewhere (25) and in the same Greek ED patient cohort (26). The current study therefore focused on the performance of the severity risk score.…”
Section: Introductionmentioning
confidence: 99%
“…PROMPT is a confirmatory study in another healthcare setting testing, however, another platform of measurement of HBP than the previous studies and aiming to use HBP as a tool for screening of the risk of early death and not of general unfavorable outcome. (10).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatix Bacterial Viral Noninfected version 3 (IMX-BVN-3) is a host messenger RNA (mRNA)-based classifier to determine the likelihood of a bacterial infection and the likelihood of a viral infection [7,8]. Several clinical studies have demonstrated its high accuracy for the detection of bacterial and/or viral infections [9][10][11][12].…”
mentioning
confidence: 99%